Psychophysical Studies of Interleaving Narrowband Tactile Stimuli to Achieve Broadband Perceptual Effects - Martinez, Juan S.; Tan, Hong Z.; Cholewiak, Roger W. (Frontiers in Virtual Reality, 2022)
Despite the ubiquitous presence of tactile actuators (tactors) in mobile devices, there is a continuing need for more advanced tactors that can cover the entire frequency range of human tactile perception. Broadband tactors can increase information transmission and enrich sensory experience. The engineering challenges are multifold in that the ideal tactors should exhibit an effective bandwidth of at least 300 Hz, small form factor, robustness, power efficiency and low cost. For wearable applications, there are the additional challenges of ease of mounting and maintaining adequate skin contact during body movements. We propose an approach to interleave narrowband tactile stimuli to achieve broadband effects, taking advantage of the limited spatial resolution of the skin on the torso and limbs. Three psychophysical experiments were conducted to assess the validity of this approach. Participants performed pairwise discriminations of two broadband stimuli delivered using one or two tactors. The broadband stimuli consisted of one mid-frequency and one high-frequency component delivered through one tactor by mixing the two components, or through two tactors (one component per tactor). The first two experiments revealed extraneous cues such as localization and mutual masking of mid- and high-frequency components that were subsequently eliminated in the third experiment. Results from 12 participants confirmed that performance on pairwise comparisons was below the discrimination threshold, confirming that broadband haptic effects can be achieved through narrowband tactors placed within the skin’s two-point limen.